Modelling and monitoring nonlinear acoustic phenomena in high-intensity focused ultrasound therapy - Jackson, E (2015)
High intensity focused ultrasound (HIFU) provides a wide range of noninvasive therapies ranging from drug delivery to the destruction of kidney stones. In particular, thermal ablation by HIFU presents an effective noninvasive method for the treatment of deep seated solid tumours. HIFU’s further uptake is limited by a need for improved treatment planning and monitoring. Two nonlinear acoustic phenomena that play key roles in HIFU treatment: finite amplitude effects that lead to the generation of harmonics and steepening of wavefronts, and acoustic cavitation. The former must be taken into careful consideration for treatment planning purposes, while the latter has the potential to provide fast, real-time, cost effective treatment monitoring. The first half of this thesis provides new measurements for the nonlinear acoustic properties of tissue, assesses the validity of two common modelling techniques for simulating HIFU fields. The second half develops a new method for combining passive acoustic mapping- an ultrasound monitoring technique- with MR thermometry, to assess estimates of cavitation enhanced heating derived from passive acoustic maps. In the first results chapter B/A was measured in ex-vivo bovine liver, over a heating/ cooling cycle replicating temperatures reached during HIFU ablation, adapting a finite amplitude insertion technique (FAIS), which also allowed for measurement of sound-speed and attenuation. The method measures the nonlinear progression of a plane-wave through liver and B/A was chosen so that numerical simulations matched measured waveforms. Results showed that attenuation initially decreased with heating then increased after denaturation, sound-speed initially increased with temperature and then decreased, and B/A showed an increase with temperature but no significant post-heating change. These data disagree with other reports that show a significant change and suggest that any nonlinear enhancement in the received ultrasound signal post-treatment is likely due to acoustic cavitation rather than changes in tissue nonlinearity. In the second results chapter two common methods of modelling HIFU fields were compared with hydrophone measurements of nonlinear HIFU fields at a range of frequencies and pressures. The two methods usedwere the KZK equation and the commercial package PZFlex. The KZK equation has become the standard method for modelling focused fields, while the validity of PZFlex for modelling these types of transducers is unclear. The results show that the KZK equation is able to match hydrophone measurements, but that PZFlex underestimates the magnitude of the harmonics. Higher order harmonics in PZFlex are not the correct shape, and do not peak around the focus. PZFlex performs worse at higher pressures and frequencies, and should be used with caution. In the final two chapters a system for estimating cavitation-enhanced heating from acoustic maps is developed and benchmarked against magnetic resonance thermometry methods. The first chapter shows that the ultrasound and MR monitoring systems are compatible, and registers the two imaging systems. The HIFUfocus is clearly visible in passive maps acquired in the absence of cavitation and these coincide with the centre of heating in MR temperature images. When cavitation occurs, it coincides spatially and temporally with the appearance of a clear spike in temperature, especially when the passive maps are processed using the Robust Capon Beamformer algorithm. The final chapter shows how passive maps can be converted into thermal heating inputs, and used to estimate cavitation-enhanced temperature increases. These estimates have the potential to closely match maximum temperature rise, and estimated thermal dose after the estimated temperature rise is spatially averaged. However, themethod is not always successful. This is partly due to uncertainties in MR thermometry estimates, partly due to uncertainties in the acoustic properties of tissue.